A collateral circulation in ischemic stroke accelerates recanalization due to lower clot compaction. - Sandra Thalerová; Andrea Vítečková Wünschová; Patrícia Kittová; Lucie Vašátková; Michaela Pešková; Ondřej Volný; Anna Mac Gillavry Danylevska; Jan Víteček; Lukáš Kubala; Robert Mikulík (PLoS ONE)
Collaterals improve recanalization in acute ischemic stroke patients treated with intravenous thrombolysis, but the mechanisms are poorly understood. To investigate it, an in vitro flow model of the middle cerebral artery was developed with or without collaterals. An occlusion was achieved using human blood clots. Recanalization time, thrombolysis (clot length decrease and red blood cell (RBC) release), pressure gradient across the clot and clot compaction were measured. Results showed that with or without collateral alteplase-treated RBC dominant clots showed recanalization time 98±23 min vs 130±35 min (difference 32 min, 95% CI -6-58 min), relative clot reduction 31.8±14.9% vs 30.3±13.2% (difference 1.5%, 95% CI 10.4-13.4%) and RBC release 0.30±0.07 vs 0.27±0.09 (difference 0.03, 95% CI 0.04-0.10). Similar results were observed with fibrin-dominant clots. In RBC dominant clots, the presence vs absence of collateral caused different pressure gradients across the clot 0.41±0.09 vs 0.70±0.09 mmHg (difference 0.29 mmHg, 95% CI -0.17-0.41 mmHg), and caused the reduction of initial clot compaction by 5%. These findings align with observations in patients, where collaterals shortened recanalization time. However, collaterals did not increase thrombolysis. Instead, they decreased the pressure gradient across the clot, resulting in less clot compaction and easier distal displacement of the clot.